Plumb, Guyton and path: polysemy of health from the perspective of college students - Marieli Mezari Vitali; Maria Fernanda Araújo; Fabiane Ferraz; Luciane Bisognin Ceretta; Jacks Soratto (2019)
ABSTRACT Purpose: to identify the understanding of health of college students enrolled in health programs of a university in the South of Brazil. Methods: a qualitative, descriptive and exploratory research conducted by means of an online questionnaire with students of health programs. The data were analyzed according to the thematic content analysis with the aid of Atlas.ti software. Results: there were 233 answers, structured in 20 codes, 7 subcategories and 3 categories: health associated with well-being, balance and quality of life; health connected with the biological and absence of diseases; and health related to the capacity to act and the notion of wholesomeness. Conclusion: the understanding of health for college students is expressed in a polysemic way, but with a predominating comprehension linked to the notion of well-being and balance.